Effect of deboning time on the quality of broiler breast meat (Pectoralis major) - PA Souza; LM Kodawara; ERL Pelicano; HBA Souza; A Oba; FR Leonel; EA Norkus; TMA Lima (Brazilian Journal of Poultry Science, 2005)
The present study evaluated the effect of different deboning times on the quality of broiler breast meat. Seventy-two broiler breasts were evaluated. They were distributed in a completely randomized experimental design, with six treatments, six repetitions and two birds per parcel. The treatments were denominated as follows: A - deboning immediately after chilling, B - deboning 1 h after chilling, C - deboning 2 h after chilling, D - deboning 3 h after chilling, E - deboning 4 h after chilling, and F - deboning 24 hours after chilling. Lowest pH values (p<0.05) were seen when deboning was performed 24 h after carcass chilling (pH=6.00) in comparison to deboning at 0 h (6.69) and 1 h (6.42) after chilling. R values were inversely proportional to pH values, i.e., R values were lower (p<0.05) in treatments A (1.05) and B (1.07) when compared to treatment F (1.44). No differences were seen in cooking loss during thermal treatment (broiling) of the muscle P. major. Higher shear forces (p<0.05) were seen in broiled muscles from carcasses with shorter storage times (A - 11.78 kgf and B - 10.75 kgf) before deboning, when compared to treatments E (6.11 kgf) and F (5.64 kgf). Higher L* values were observed in the treatment in which carcass deboning was performed 24 hours after chilling (49.26) in comparison to deboning immediately after chilling (44.68). Therefore, it was concluded that an interval of at least 4 hours is needed between chilling and deboning to obtain broiled breast fillets with tender texture. Furthermore, paler meat color (L* value) was produced with longer carcass storage before deboning.